Development of a soft sensor for a batch distillation column using support vector regression techniques - Jain, P.; Rahman, I.; Kulkarni, B. D. (Chemical Engineering Research & Design, 2007)
A support vector regression (SVR)-based model is developed for a batch distillation process in order to estimate the product compositions from temperature measurements. Kernel function such as linear, polynomial and RBF are employed for SVR modelling. The original process data was generated by simulating the batch distillation process, varying the initial feed composition and boilup rate from batch to batch. Within each batch reflux ratio was also randomly changed to represent the true dynamics of the batch distillation. The results show the potential of the method for developing softsensor for chemical processes.
Keywords: Batch distillation; composition estimation; soft sensor; support vector regression

Au based Ni and Co bimetallic core shell nanocatalysts for room temperature selective decomposition of hydrous hydrazine to hydrogen - Jain, P.; Anila, K. A.; Vinod, C. P. (ChemistrySelect, 2019)
Nickel and Cobalt bimetallic catalysts with Au as core metal has been synthesized and demonstrated for hydrazine decomposition reaction for producing hydrogen. Gold-cobalt and gold nickel bimetallic system belonging to the class of strained structures with high lattice mismatch of approximately 14% are demonstrated for synergistic effects atypical of monometallic counterparts for the selective decomposition of hydrous hydrazine to H-2 with N-2 as the other product at room temperature.
Keywords: (HDR); Au@Co.; Au@Ni.; Bimetallic; catalyst.; core; decomposition; Hydrazine; nanoparticles.; reaction; shell

Unprecedented stability in Au@Co core-shell bimetallic catalyst supported on SBA-15 (Au@Co/SBA-15) for atmospheric pressure CO hydrogenation - Jain, P.; Chimote, M.; Vinod, C. P. (Materials Today Sustainability, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Bimetallic nanoparticles demonstrating <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/synergistic-effect" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about synergistic effect from ScienceDirect's AI-generated Topic Pages">synergistic effect (electronic or geometric modification) often show distinct chemical and physical properties compared with the parent metals. In catalysis, this provides opportunities to engineer solid materials with appreciable activity, selectivity, and stability. In the present study, we have synthesized Au@Co core–shell bimetallic nanoparticles by colloidal synthesis approach with a focus to study and explore the synergistic effect between Au and Co in Au@Co <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/bimetallic-catalyst" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about bimetallic catalyst from ScienceDirect's AI-generated Topic Pages">bimetallic catalyst supported on SBA-15 on <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/fischer-tropsch" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px; font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;" title="Learn more about Fischer Tropsch from ScienceDirect's AI-generated Topic Pages">Fischer Tropsch<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> (FT) reaction. The deactivation of catalyst is a significant drawback in CO hydrogenation (syngas conversion/FT synthesis), and the present study provides the design of a new material, which resists the surface cobalt oxide formation and inactive coke formation and gives efficient CO conversion with high stability.